1999
DOI: 10.1017/s095375629800700x
|View full text |Cite
|
Sign up to set email alerts
|

A cytological and ultrastructural study on the maturation and germination of oospores of Plasmopara viticola from overwintering vine leaves

Abstract: Observations on cytological and ultrastructural changes in Plasmopara viticola oospores were carried out during the overwintering period. Three types of oospores were observed. Type I, characterized by a thin inner oospore wall (IOW), large lipid globules and two nuclei, was recovered only in samples collected in October. These oospores were considered to be immature. Maturation occurred during November and involved a noticeable increase in thickness of the IOW, fusion of nuclei, formation of an ooplast and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 16 publications
(25 reference statements)
6
46
0
1
Order By: Relevance
“…Calcium, and, consequently, germination rate exhibit an oscillating behaviour nutritional reserves. Ultrastructural studies have shown that P. viticola oospores are mature by the middle of November (Vercesi et al 1999). In fact the germination of the oospores overwintered in natural conditions occurs from the end of November onwards, continuously until mid May and then sporadically until mid June.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium, and, consequently, germination rate exhibit an oscillating behaviour nutritional reserves. Ultrastructural studies have shown that P. viticola oospores are mature by the middle of November (Vercesi et al 1999). In fact the germination of the oospores overwintered in natural conditions occurs from the end of November onwards, continuously until mid May and then sporadically until mid June.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual propagation exists prior to overwintering of infectious spores, which are of agronomic importance as they provide the first source of inoculum in the year. However, it is the rapid sequence of asexual propagation cycles (sometimes as short as 4 days) that is responsible for the efficient spread of this oomycete during the growing season (Vercesi et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, knowledge of the amount of the previous germination percentage G~ 1 is useful to achieve a more satisfactory correlation. The previous germination percentages assessed in the current year include a precocious climatic influence, probably affecting oospore maturation (VERCESI et al, 1999). BURRUANO et al (1994a) observed that the oospore germination rate is strictly dependent on the number of mononucleate (e.g.…”
Section: Discussionmentioning
confidence: 99%